2015
DOI: 10.6061/clinics/2015(08)05
|View full text |Cite
|
Sign up to set email alerts
|

The effect of elemene on lung adenocarcinoma A549 cell radiosensitivity and elucidation of its mechanism

Abstract: OBJECTIVE:To investigate the effect of elemene on the radiosensitivity of A549 cells and its possible molecular mechanism.METHODS:Apoptosis of A549 cells was detected by flow cytometry and fluorescence microscopy. The effect of double-strand break (DSB) damage repair in A549 cells was evaluated using the neutral comet assay. Protein expression levels were detected using western blotting, and the correlation between protein levels was analyzed.RESULTS:Elemene exhibited a radiosensitizing effect on A549 cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Jiang et al 15 showed that, in addition to promoting tumour cell apoptosis directly, β-elemene also exerts a radiosensitizing effect on lung adenocarcinoma A549 cells through upregulation of p53 expression and inhibition of Bcl-2 expression. Another study by Zou et al 16 demonstrated that the molecular mechanisms responsible for the radiosensitizing effect might involve the downregulation of dna-dependent protein kinase catalytic subunit gene expression. Li et al 17 established a lung tumour model in female athymic BALB/cnu/nu mice, and showed that β-elemene (45 mg/kg) had the potential to reduce radiation-induced expression of survivin and hypoxia inducible factor 1a proteins, which were probably the targets of β-elemene.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al 15 showed that, in addition to promoting tumour cell apoptosis directly, β-elemene also exerts a radiosensitizing effect on lung adenocarcinoma A549 cells through upregulation of p53 expression and inhibition of Bcl-2 expression. Another study by Zou et al 16 demonstrated that the molecular mechanisms responsible for the radiosensitizing effect might involve the downregulation of dna-dependent protein kinase catalytic subunit gene expression. Li et al 17 established a lung tumour model in female athymic BALB/cnu/nu mice, and showed that β-elemene (45 mg/kg) had the potential to reduce radiation-induced expression of survivin and hypoxia inducible factor 1a proteins, which were probably the targets of β-elemene.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed mechanistic insights unraveled that β-elemene in combination with radiation drastically reduced protein levels of DNA damage repair associated kinase (DNA-PKcs). 37 ATM played a major role in the DNA damage response and repair. Treatment of glioblastoma cells with β-elemene decreased the phosphorylation of ATM, PKB/AKT, and ERK following chemotherapy or radiotherapy.…”
Section: Regulation Of Atm Kinase By β-Elemenementioning
confidence: 99%
“…Elemene, extracted from Rhizoma Zedoariae, is a terpene compound with an immunomodulatory effect, and the radiosensitization of β-elemene has been confirmed as the main anti-tumor component of elemene. 3 Although it has multiple effects such as the inhibition of tumor angiogenesis, promotion of tumor cell G-M phase arrest, induction of tumor cell apoptosis, and repairment of Deoxyribonucleic acid (DNA) double-strand damage, [4][5][6] its sensitizing mechanism still remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%